Theory of Operator Algebra II - Masamichi Takesaki (New York Springer, 2003)
School of Mathematics and Natural Science
MIR No.: 202
Order Date: 2024-08-07
Order No: CU/OPEX/LIBRARY/24/2024-25
Received Date: 2024-09-05
Keywords: Mathematics, Algebra,Operator algebras